The Aging Endurance Athlete: An Analysis of the Latest Evidence for Optimal Training Schedules, Expected Gains, and Recovery Strategies. Issue 1 (January 2016) - Studer, Mike
Abstract : Masters athletes' (aged 40 years and older) performance in endurance competition continues to improve and exceed that of previous decades. In this article, we will address the training and recovery strategies that are behind this trend of improving performance of aging endurance athletes. Specifically within this population, we will address research on maintaining and gaining muscular strength with age, including evidence on prescriptions and expectations, as well as recovery strategies affording optimal participation in training. Finally, we turn the discussion toward the referenced improved performance investigating both how this trend has transpired and postulating the apex of this curve.